Water Quality Index (WQI) for Main Source of Drinking Water (Karaçomak Dam) in Kastamonu City, Turkey - Imneisi, Idris Basher; Aydin, Mirac (OMICS Publishing Group, 2016)
Karacomak Dam is main source of drinking water in Kastamonu city (Turkey) for this reason, In this study used Water quality index which provides a single value to express overall quality based on 13 variables that were determined during the period between September 2015 until July 2016. Sampling points chosen as described by first station at intake point of the drinking water supply for Kastamonu city, second station was opposite intake point of the drinking water supply about (449) m along at main dam. The parameters namely Electrical Conductivity (EC), pH, Temperature (T), Dissolved oxygen (DO), Turbidity (TUR), Total hardness (Ha), Total alkalinity, Ammonia nitrogen (NH4-N), Nitrite nitrogen (NO2-N), Nitrate nitrogen (NO3-N), Phosphate (PO4-P), Biochemical oxygen demand (BOD), Chemical oxygen demand (COD) were analyzed according to Standard Methods for the Examination of Water and Wastewater. The resulted WQI shows that (35.5 and 32.4) for sites (S1 and S2) respectively. On the other hand, there was significant temporal variations in water quality index among poor quality to excellent quality whereas that January 2016 showed high level of deterioration at (S1, S2), this may be due to starting the winter 2016 where high contribution from runoff at downstream areas which increase of deterioration body water in the Dam. The results clearly show that Water Quality index (WQI) was useful tool to obtain the right decision and evaluating water quality. In future, evaluation of water quality in Karacomak dam should be given main priority of using the microbiological parameters with physico-chemical parameters in WQI calculations and to water quality monitoring.
Keywords: 13. Climate action; 11. Sustainability; 14. Life underwater; 6. Clean water